Moderating effects of regional disparities on the relationship between individual determinants and public health service utilization among internal migrants: evidence from the China migrant dynamic survey in 2017 - Zhen Yang; Cheng-hua Jiang; Jiansheng Hu (BMC, 2022)
Abstract Background Regional disparities and individual determinants have a significant impact on the accessibility of national essential public health services (NEPHS) for internal migrants (IMs) Nevertheless, few studies have explored the interaction between these two factors. Method A cross-sectional sample of 102,632 IMs from the 2017 China Migrant Dynamic Survey was selected. The 28 provinces were divided into high-income provinces (HIPs) and low and middle-income provinces (LMIPs) according to their per capita disposable income (PCDI). Logistic regression was conducted using sex, residence duration, education, community type, migration range, social participation and relative personal income as independent variables, NEPHS awareness and health records registration (HRR) as dependent variables, and regional economic development level (REDL) as a moderating variable. Results The rate of NEPHS awareness and HRR in HIPs (60.7, 30.6%) were lower (x2 = 42.486, p < 0.001; x2 = 25.573, p < 0.001) than those in LMIPs (62.9, 32.2%). After controlling for other variables, NEPHS awareness (OR = 1.379, p < 0.001) and HRR (OR = 1.661, p < 0.001) of IMs in HIPs were higher. Sub-group proportion of education Ms. in HIPs were higher. Sub-group = 1.379, p < 0.001) and HRR dependent mong internal migrants:, 61.0, 42.2%) were higher than those in LMIPs (60.4, 19.7, 35.8, 25.5%). Among urban communities, intra-provincial migration, social participation, education > 9 years, and middle-income, the protective effect of the first three factors on NEPHS awareness was greater in HIPs (OR = 1.386, p < 0.001; OR = 1.383, p < 0.001; OR = 2.008, p < 0.001) than in LMIPs (OR = 1.053, p < 0.001; OR = 1.109, p < 0.001; OR = 1.861, p < 0.001), while the effect of all five factors on HRR was greater in HIPs (OR = 1.440, p < 0.001; OR = 1.380, p < 0.001; OR = 1.895, p < 0.001; OR = 1.148, p < 0.001; OR = 1.146, p < 0.001) than in LMIPs (OR = 1.045, p < 0.05; OR = 1.169, p < 0.001; OR = 1.677, p < 0.001; OR = 1.027, p > 0.05; OR = 1.028, p > 0.05). Conclusions REDL directly affected the NEPHS utilization of IMs, and the negative effects of vulnerable characteristics on the NEPHS utilization of IMs were amplified in HIPs. The government is urged to regard IMs with vulnerable characteristics in HIPs as the key population in future NEPHS equalization and take targeted measures to stimulate their enthusiasm to participate in NEPHS.